Pengaruh Kemampuan Berpikir Kritis & Literasi Digital terhadap Wawasan Kebangsaan - . Mukhzamilah; Subuh Isnur Haryudo; Ahmad Bashri; Syamsul Shodiq (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2023)
This study aims to determine the effect of critical thinking skills and digital literacy on national insight. The method used in this study is a quantitative method by testing the validity and reliability. The data collection method in this study used a questionnaire distribution method to rural youth in Sidoarjo. The results of this study are the relationship between critical thinking and nationalism in Sidoarjo rural youth showing a path or original sample value of 0.594 and showing a positive relationship, the t-count value is 4.773 higher than the P value of 1.96 and lower than the Sig value of 0.004, which is less than 0.05, indicating that critical thinking has a positive value and a significant effect on the national insight of rural youth. Whereas in the relationship between digital literacy and national insight, the path value (original sample) is 0.208, reflecting a positive relationship, with a t-count value of 4.773 higher than t-table 1.96 and lower than the Sig value. 0.00 which is less than 0.05, indicating a positive and statistically significant relationship between digital literacy and national insight among young people.